How to do everything with Web 2.0 mashups - Feiler, Jesse (McGraw-Hill, 2008)
Want to supercharge your website with the latest searching, mapping, shopping, and imaging tools? Now you can build amazing mashups with help from this step-by-step guide. How to Do Everything with Web 2.0 Mashups shows you how to remix the best of Google, Amazon, Flickr, and eBay to create customized applications. You'll learn to use essential Web 2.0 technologies--including XML, JavaScript, XHTML, and REST--and seamlessly integrate them into your own innovative mashups.